P419 Frequency of inadequate response to anti-tumour necrosis factor therapy in patients with ulcerative colitis. Preliminary results from POLIBD study. (16th January 2018) - Pekala, A; Filip, R
Abstract: Background: Therapeutic drug monitoring (TDM) may positively impact therapeutic decisions in patients with inflammatory bowel disease (IBD), especially in those who lose response to anti-tumour necrosis factor (TNF) therapy. The aim of the study was to evaluate the frequency of inadequate response to anti-tumour necrosis factor therapy in polish patients with ulcerative colitis. Mutual relationship between the lack of response, serum trough level of IFX and ADAs was also evaluated. Methods: In total, 65 UC patients (33 male/32 female, 18–69 age; UC 3.5 years; duration of biosimilar IFX CT-P13 therapy from 6 to 30 weeks) were enrolled in this consecutive cohort from the referral IBD centre in Poland. Previous and current therapy, laboratory data and clinical activity at the time of trough level (TL) and antidrug antibody (ADA) measurement were recorded. All patients received standard immunosuppression with no additional steroid nor antibiotic therapy. TDM was performed before third induction dose, 4 and 6 weeks after it and before the first maintenance dose as well as at the time of suspected loss of response (LOR) using ELISA tests (Janssen Biotech, Horsham, PA, USA). Results: In total, 65 UC patients who were induced with CT-P13, 51 (78%) responded to therapy. Of those who did not archived remission 22 (33%), 11 (17%) partially responded, in another 11 (17%) no response was noticed. In 3 (4.6%) patients SAE, that forced the withdrawal of treatment, was recorded. From 11 patients with no response, 8 (72%) had an IFX levels below therapeutic values, while the remaining 3 (27%) had IFX levels within the therapeutic values (3–7 µg/ml). Of these patients, 2 (18%) patients had detectable ADAs with the range from 2.8 to 4.2 IU/ml (normal value <2 IU/ml). From all who responded to the induction regimen, nearly 78% maintained their remission at Week 30, except 1 patient with secondary LOR at Week 16 (low TL of IFX, no ADAs detected). Conclusions: Approximately one-fifth of UC patients did not respond to the induction with biosimilar anti-TNF CT-P13 therapy. Although positive correlation of serum through levels of IFX with the clinical response was found, however the role of ADAs in those who did not archived remission was negligible.